What is Existential Educational Encounter? - Koskela, Jani; Siljander, Pauli (Paideusis, 2014)
This paper aims to clarify the meaning of the pedagogical concept of encounter by providing an overview of its use from the historical foundations of the concept in Otto Friedrich Bollnow’s (1903 to 1991) philosophy to contemporary phenomenological readings by Maxine Greene, Donald Vandenberg and Robyn Harrison. The outcome is a critical analysis and evaluation of the significance of the concept in educational contexts. The aims of the paper are as follows: a) to articulate the educational significance of the concept of encounter, and b) to clarify its relationship to the humanistic concept of formation (or unfolding; Bildung), in order to establish the tension between Bildung-theory and the existential theory of human formation. The paper claims that, for a more elaborated understanding of the human educative process, the tension between the processes of encounter and Bildung should be seen as the core tension behind the holistic view of becoming human. Also, c) for an analysis of the Anglo-American reception of the concept, a phenomenological view of the encounter as a transcendental aspect of a learning process will be made in order to gain a wider view of the concept.